Small Folklore Genres in Humanistic Attitude to Personality - Makarenko, Olha (Pedagogical Discourse, 2012)
Ethno-pedagogical aspects of formation of preschoolers are analyzed in the article. Special attention is paid to the role of small folklore genres in humanistic education.